'This funny place': Uncovering the ambiguity of saltmarshes using a multimodal approach. Issue 3 (21st March 2022) - Thomas, Merryn; Roberts, Erin; Pidgeon, Nick; Henwood, Karen
Abstract: Saltmarshes are increasingly recognised for the range of benefits they offer, including coastal protection, flood regulation and carbon sequestration. However, much less is known about how people perceive these environments and their importance for non‐material aspects of human well‐being. As climate change and sea‐level rise render these environments increasingly vulnerable, there is a need to better understand how saltmarshes are valued. This is because these values influence—and are influenced by—the ways in which people interact with places and therefore gain well‐being benefits from them. These values also shape management decisions, which in turn affect the well‐being of people and environment. To address this need, we use a multimodal qualitative approach (mobile interviews, photo elicitations, mapping and word association) to explore the values held in connection to saltmarshes at two Welsh case study sites: the Taf Estuary in Carmarthenshire and the Mawddach Estuary in Gwynedd. We find that saltmarshes are ambiguous places, not having one obvious meaning, and being open to more than one interpretation. They are both known and unknown; valued and (literally) overlooked. We suggest that this ambiguousness is related to both the physical characteristics of saltmarshes, which change and shift on short and long time‐scales, as well as to the ways in which people (can) relate with them. We discuss how ambiguity renders saltmarshes as places of exclusive, privileged human–nature relationships, and reflect on the implications of our findings for human well‐being and the management of threatened environments. We also consider how multimodal, in‐depth and place‐based methods such as ours provide ways in which to explore the more intangible and changeable values associated with particular habitats. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Crynodeb: Mae cydnabyddiaeth am yr amrywiaeth o fanteision a gynigir gan forfeydd heli ‐ megis diogelu'r arfordir, rheoli llifogydd a storio carbon – ar gynnydd. Fodd bynnag, ni wyddom lawer am y ffyrdd y mae pobl yn canfod y cynefinoedd hyn, a'u pwysigrwydd o ran agweddau ansylweddol ar gyfer lles dynol. Wrth i newid hinsawdd a chynnydd yn lefel y môr fygwth dyfodol y cynefinoedd hyn, mae angen gwell dealltwriaeth o sut mae pobl yn gwerthfawrogi morfeydd heli, gan fod y gwerthoedd hyn yn dylanwadu ‐ ac yn cael eu dylanwadu gan‐ y ffyrdd y mae pobl yn rhyngweithio â lleoedd, ac yn derbyn buddion lles ohonynt. Mae'r gwerthoedd hyn hefyd yn llunio penderfyniadau rheolaeth amgylcheddol sydd, yn eu tro, yn effeithio ar les pobl a chynefinoedd. Er mwyn mynd i'r afael â'r angen hwn, defnyddid dull ansoddol amlfodd (cyfweliadau symudol, a thasgau tynnu lluniau, mapio, a chysylltu geiriau) i archwilio'r gwerthoedd sy'n gysylltadwy â morfeydd heli ar ddau safle astudiaeth achos yng Nghymru: Moryd y Taf yn Sir Gaerfyrddin a Moryd y Fawddach yng Ngwynedd. Darganfyddom fod morfeydd heli yn lleoedd amwys, heb un ystyr amlwg, a'u bod yn agored i fwy nag un dehongliad. Maent yn hysbys ac yn anhysbys; yn cael eu gwerthfawrogi ac yn cael eu hanwybyddu. Awgrymwn fod yr amwyster hwn yn gysylltiedig â nodweddion ffisegol y morfeydd eu hunain ‐ sy'n trawsnewid ar raddfeydd amser byr a hir ‐ yn ogystal â'r gwahanol ffyrdd gall bobl uniaethu â nhw. Trafodwn sut mae amwyster yn gwneud morfeydd heli yn fannau lle mae perthnasoedd dynol‐natur unigryw a freintiedig, a myfyriwn ar oblygiadau ein canfyddiadau ar gyfer lles dynol a rheolaeth cynefinoedd dan fygythiad. Ystyriwn hefyd sut mae dulliau ansoddol amlfodd sy'n seiliedig ar le, fel ein dulliau ni, yn galluogi ffyrdd o archwilio'r gwerthoedd mwy anniriaethol a chyfnewidiol sy'n gysylltiedig â chynefinoedd penodol.